2001
DOI: 10.1002/ps.398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some granular insecticides currently used for the treatment of maize crops (Zea mays) on the survival of inoculated Azospirillum lipoferum

Abstract: Four insecticides, carbofuran, chlormephos, terbufos and benfuracarb, currently used on maize (Zea mays) at sowing, were tested for their compatibility with Azospirillum lipoferum strain CRT1 used as an inoculant to improve maize growth and yield. The growth or survival of A lipoferum was studied in the presence of the insecticides: (1) in liquid and solid cultures of the bacteria, (2) when a commercial inoculant (Azogreen-m, Liphatech, Meyzieu, France) was inoculated directly on insecticide granules, (3) when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Of 4 insecticides (carbofuran, chlormephos, terbufos, and benfuracarb) currently used on maize at the time of sowing, only terbufos had a slight effect on growth of A. lipoferum in solid medium cultures. Physical contact of the insecticides with the commercial inoculant (Azogreen-m), bacteria inoculated directly on insecticide granules, or inoculant mixed with an insecticide all decreased survival of A. lipoferum (Revellin et al 2001).…”
Section: Insecticidesmentioning
confidence: 98%
“…Of 4 insecticides (carbofuran, chlormephos, terbufos, and benfuracarb) currently used on maize at the time of sowing, only terbufos had a slight effect on growth of A. lipoferum in solid medium cultures. Physical contact of the insecticides with the commercial inoculant (Azogreen-m), bacteria inoculated directly on insecticide granules, or inoculant mixed with an insecticide all decreased survival of A. lipoferum (Revellin et al 2001).…”
Section: Insecticidesmentioning
confidence: 98%
“…This survey revealed that about 85% respondent had no confidence toward biofertilizers practices while half of the 85% respondents reported that lack of knowledge about biofertilizers was reason for unacceptability of this technology. Therefore, in order to make full use of biofertilizers and to compete with synthetic fertilizers, there is need to consistently generate awareness among farmers by organizing various community programs (Revellin et al, 2001). The timely supply of cultures in distant areas, slow response of biofertilizers and availability of poor quality PGPR inocula in commercial market are other major problems in popularization and adoption of biofertilizers.…”
Section: Pgpr Inoculant Development and Productionmentioning
confidence: 99%
“…Communication gap and miscommunication of the farmers by some commercial producers also is a considerable constraint. Lack of storage and marketing facilities, consistent awareness in the farmers by conducting community programs is still welcome [14]. As the production and distribution of biofertilizers is seasonal, the commercial production units may suffer from lack of demand.…”
Section: Lack Of Awarenessmentioning
confidence: 99%